Investigation of nanostructured titanium oxide from surface sol-gel processing for biomaterial applications - Advincula, Maria Athena C. (ProQuest Dissertations & Theses Global, 2004)
"The overall goal was an in-depth study of an adaptation of the surface sol-gel process as a nanometer-precise method to prepare nanostructured titanium oxides for biomedical applications. The surface topography, chemistry, wettability, and mechanical strength of the sol-gel film were first systematically investigated on model substrates (silicon wafer, gold-coated quartz). The sol-gel coating was predominantly Ti0₂ with abundant hydroxyl groups. The topography was nanoporous, amorphous, and rough. The sol-gel film was hydrophilic (surface energy > 60 dyne/cm) and increased in hydrophilicity and nanoroughness with increasing oxide thickness. The hardness and Young's modulus of the film increased with oxide thickness and heat treatment. A preliminary study of albumin bioadhesion on sol-gel film modified with self-assembled monolayers (SAMs) showed significant change in wettability, topography, thickness, and coverage of protein, which was consistent with the chemistry and packing of the functionalized underlayer. Furthermore, the size and resolution of patterned sol-gel film on gold substrates by microcontact printing was dependent on the surface properties of the sol-gel film and the uniformity of the thiol layers. The sol-gel films deposited on titanium and T16A14V were also predominantly TiC>2, and were amorphous with titanium precipitates and mesopores (2-50 nm). The wetability and roughness also increased with oxide thickness. The corrosion resistance, adhesive strength of the film, and release of ions from coated Ti6A14V substrate were not significantly different from conventionally oxidized (passivated) substrates, although the precipitation of calcium and phosphate from simulated body fluid was higher on the solgel film after 14 days. Higher cellular attachment at 1 and 24 h and mineralization were also found on the sol-gel coated substrates. Sol-gel films modified with chitosan or polyethylene glycol by electrostatic layer-by-layer deposition (LbL) and SAMs, respectively, showed different chemistry, topography, and cellular attachment, consistent with the chemistry and conformation of immobilized molecules. Furthermore, sol-gel imprinted with Arg-Gly-Asp (RGD) peptides demonstrated selective recognition and specificity of integrin binding. Thus, surface sol-gel processing and the biofunctionalization of titanium oxide can be utilized to further enhance the biocompatibility of this biomaterial for biomedical applications."--Abstract.